1998
DOI: 10.1257/jep.12.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Job Displacement

Abstract: The past decade and a half has seen tremendous research growth in the area of job displacement. This paper discusses the state of knowledge on the issues and questions of job loss. The 1984-96 Displaced Worker Surveys are used to describe how the characteristics of displacement are changing to include more college educated, white collar, and nonmanufacturing workers. For many workers, the long-term earnings losses following displacement are large due to the loss of firm-specific human capital. More research is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
286
2
12

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(323 citation statements)
references
References 25 publications
14
286
2
12
Order By: Relevance
“…Furthermore, as mentioned, for example, by Schwerdt (2011), labor turnover before exit should also be taken into account when examining the effects of displacement on labor market outcomes like earnings. The upshot is that it may be misleading to regard firm exits as exogenous shocks that are unrelated to worker characteristics, as it is often assumed in the literature (see e.g., Kletzer, 1998;Farber, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as mentioned, for example, by Schwerdt (2011), labor turnover before exit should also be taken into account when examining the effects of displacement on labor market outcomes like earnings. The upshot is that it may be misleading to regard firm exits as exogenous shocks that are unrelated to worker characteristics, as it is often assumed in the literature (see e.g., Kletzer, 1998;Farber, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Displaced workers have been the subject of an extensive literature (see surveys by Fallick, 1996, andKletzer, 1998). The basic stylised facts are: 1) displaced workers experience longer unemployment spells and higher earning losses than the other unemployed workers (Swaim andPodgursky, 1991, Jacobson et al, 1993); 2) the duration of the subsequent unemployment spell increases with job tenure (Fallick, 1996), because workers with high tenure have a higher level of specific human capital investment in their firms and in their industry or occupational sectors; 3) the duration of this unemployment spell is affected by the cause of displacement; for instance, Swaim and Podgursky (1991) found that workers displaced because of plant closures experience one third fewer weeks of unemployment than those who are laid off by ongoing establishments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dar and Gill (1998), after studying eleven retraining programs in six countries, concluded that such programs are generally no more effective than job search assistance in increasing re-employment prospects. As a result, they should be targeted to those who can benefit the most from them: women and minorities (Moore, 1990), industry-switchers (Stock, 1998), laid off workers from manufacturing (Kletzer, 1998), or those with high tenure (Jacobson et al, 1993). In fact job search assistance and training appear to have some impact on the types of jobs that displaced workers obtain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 http://www.bls.gov/news.release/disp.nr0.htm 2 For a summary of the literature on displaced workers to 1998, see Kletzer (1998). Using the Panel Study of Income Dynamics (PSID), Polsky (1999) found that the consequences of job loss worsened between the periods 1976-81 and 1986-91.…”
Section: What We Know About Displacement and Displacement Outcomesmentioning
confidence: 99%